Effects of presentation delivery rate on errors in simultaneous interpreting: A pilot study - Aulia Addinillah Arum (Indonesian Journal of Applied Linguistics, 2022)
Although the success of information rendition in simultaneous interpreting (SI) is susceptible to many factors, the speed of the source speech (SS) is perceived as one of the most challenging problem triggers. However, previous studies that examine the effects of SS in SI have reported different results. Therefore, this study aims to examine the effects of normal and fast source speech rates on simultaneous interpreting performance through error analysis. In this pilot study, seven error categories are employed, i.e., segment omission, word-and-phrase level omission, addition, unfinished sentence, filled pause, and long pause, which are derived from error classifications by Barik (1971). The first four categories are part of linguistic errors, whereas the last three categories are part of paralinguistic errors. Two videos with a speed of 124-wpm (words per minute) and 184-wpm were used as the source speeches and three professional interpreters with more than seven years of experience were recruited as research participants. It is revealed that the fast speech rate has increased the frequency of errors. Additionally, segment omission appears to be the category mostly impacted by SS speed. Therefore, the result of this study suggests interpreters’ training institutions pay more attention to coping tactics learning and acquisition in their courses.  Nevertheless, more replication studies are still required to verify this finding.